Tantangan dan Strategi Data Driven Policy di Indonesia - Bambang Aditio; Aldri Finaldi; Asnil Asnil (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the dynamics of Data Driven Policy implementation in Indonesia, which faces a disconnect between the ambitions of digital regulation and the reality of execution on the ground. Using a qualitative approach with the Three Lenses of Evidence-Based Policy analysis framework (Head, 2008), this study examines the interaction between scientific evidence, political considerations, and professional practices in government data governance. The results show that although legal infrastructure such as Satu Data Indonesia (SDI) has been established, its effectiveness is hampered by structural barriers: the dominance of sectoral egos and a culture of intuitive decision-making (political lens), as well as a mix of digital talent and resistance from a paternalistic bureaucratic culture (practical lens). These findings confirm that data fragmentation and cybersecurity incidents are not simply technical failures, but rather systemic governance failures. Therefore, this study recommends a “soft reform” strategy that integrates the enforcement of technical standards, budget incentive mechanisms, and digital leadership transformation to align data validity with the political realities of the bureaucracy.